Financial disclosure and stock price volatility: evidence from Portugal and Belgium - Vieira, Elisabete F. Simões (2012)
This paper attempts to provide evidence on the determinants of reporting transparency and its impact on stock price volatility, analysing the disclosure practices of two European countries. We proxy for transparency by manually constructing two indexes scores for the sample firms. We assess the differences in disclosure practices between Portuguese firms and a matched sample of Belgian firms, applying a transparency and a volatility model. We find evidence that Portuguese firms are less transparent then the Belgian ones, concerning the subjects of ownership and governance. The results show that larger and more profitable firms are more transparent. For separate samples of Belgian and Portuguese firms, and based on annual reports information, we find no evidence of an association between transparency and price volatility. However, considering the quarterly reports, we find a negative relation between these variables for the second quarter, suggesting that the higher the transparency, the lower the stock price volatility. Analysing two small European countries with relative lack of research contributes to the recent literature on the information transparency investigating economic consequences of variations in disclosure (stock price volatility).